The Influence of Digital Financial Services on the Financial Performance of Commercial Banks in Cameroon - Ngwengeh, Brendaline Beloke; Messomo, Elle Serge; Mbu , Sunday Agbor (European Scientific Journal, ESJ, 2021)
A strong banking industry is important in every nation and this can have a significant effect in supporting economic development through the provision of efficient financial services. Digital banking/financial services is the act of carrying out financial transactions without the use of physical cash, coins or bills. This paper sort to determine the influence of digital financial services on the financial performance of commercial banks in Cameroon. Specifically, it examined the influence of Digital Savings Services, Digital Transfers Services, Digital Withdrawals Services and Digital Payment Services on the profitability of commercial banks in Cameroon. It covers 10 out of 15 commercial banks in Cameroon. Methodologically, it made use of survey research design. Item by item analysis of the questions was used to identify the reliability of digital financial services. The Taylor linearise variance estimation technique was used to determine their influence on commercial bank profitability. Results from the study showed that digital saving services, digital withdrawal services and digital transfer services have a positive and significant influence on the profitability of commercial banks in Cameroon. Digital payment on the other hand had a negative but significant influence on commercial Bank’s Profitability at 10% level of significance. Generally, 48% of variations of profitability of commercial banks are caused by joint variations in the use of digital transfer services, Digital Savings services, Digital Withdrawal services and Digital Payment services. Consequently 0.52 or 52% of the variations in profitability are not accounted for by the study’s model on digital financial services and bank profitability but caused by the error term. Conclusively, digital financial services are a booster of commercial bank’s profit levels. Finally, the study recommended that management of banks and policy makers in the banking industry should go in for robust digital systems and services as a means to diversify their sources of income and meet up with declining profit levels.